PARTISIPASI KARANG TARUNA TERHADAP KEGIATAN MASYARAKAT MELALUI AKSI SOSIAL - Nandang Rukanda; Sri Nurhayati; Ganda Ganda (Comm-Edu (Community Education Journal), 2020)
This study raises the problem of the still low Youth Organization Participation Against Community Activities in Cikole Village, Lembang District, West West Bandung Regency. The objectives of the study are: (1) To find out the organized youth activities in Cikole Village, Lembang Subdistrict, West Bandung Regency (2) To find out the effectiveness of social actions carried out by Youth Organization (3) To find out the impact of social action by Youth Organization on community participation . This research uses descriptive research methods, data collection techniques using questionnaires, interviews, observations, and documentation studies. Research objects 50 people. The results of the research and findings show that: Youth activities with organized institutions color the lives of the people with various activities. The social action programs undertaken include (1) Collaborative Work to build villages and communities. (2) Greening the Environment. (3). Compensation for the poor, the poor and orphans. (4) Community Reading Gardens and (5) Houses for the Poor. There is a paradigm shift in thinking in people's lives by placing young people in strategic positions. The obstacle faced by Karang Taruna Cikole Village is the difficulty to synergize the various empowerments in an integrated program, funding constraints and misunderstanding among the members of the youth organization. The conclusion shows that social action carried out by Karang Taruna Cikole Village is seen as able to prosper the environment.